Społeczna odpowiedzialność przedsiębiorstw z perspektywy ekonomii dobrobytu - Doś, Anna (Annales. Etyka w Życiu Gospodarczym, 2019)
Corporate social responsibility (CSR) implies that corporations integrate social and environmental concerns in their business operations and in their interaction with their stakeholders on a voluntary basis. CSR’s component parts include: economic, legal, ethical and philanthropic responsibilities. Although social norms and ethics are inherent features of CSR the modern literature of economics and finance focuses mainly on CSR as a firm value-driver. Such narrow view may lead to the deterioration of CSR identity as well as underestimating the role of CSR in building welfare. Thus the purpose of the article is to show the role of CSR in achieving welfare improvements by considering social responsibility as a factor of prosperity and especially as a mechanism of ethically and institutionally anchored self-regulation supporting the organization of market failure correction reducing this welfare. The main thesis is that CSR brings about considerable benefits in terms of allocation efficiency, redistribution and stabilisation. The method employed is the analysis of international literature.